2004
DOI: 10.1021/jm049490m
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Corticotropin Releasing Factor 2 Receptor Selective Sauvagine Analogues for Treatment of Skeletal Muscle Atrophy

Abstract: The corticotropin release factor 2 receptor (CRF2R) has many biological activities including modulation of the stress response. Recently, we have demonstrated that CRF2R activation functions to prevent skeletal muscle wasting resulting from a variety of physiological stimuli. Thus we are interested in identifying CRF2R selective agonists with optimal pharmacological properties for use in treating muscle wasting diseases. Several CRF2R agonists are known including the frog peptide sauvagine (Svg), which display… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…[36] While being highly potent for both CRH receptors it does bind with higher affinity to CRHR 2 , it is 5-10 times more potent for these receptors than CRH. [6,8,37] It has been suggested that there is still a sauvagine like ligand in mammals that is yet to be discovered that would be the native ligand for CRHR 2 rather than Urocortin. [38] The only CRHR 1 selective natural ligand identified is ovine CRH (oCRH).…”
Section: Receptor Binding and Signallingmentioning
confidence: 99%
“…[36] While being highly potent for both CRH receptors it does bind with higher affinity to CRHR 2 , it is 5-10 times more potent for these receptors than CRH. [6,8,37] It has been suggested that there is still a sauvagine like ligand in mammals that is yet to be discovered that would be the native ligand for CRHR 2 rather than Urocortin. [38] The only CRHR 1 selective natural ligand identified is ovine CRH (oCRH).…”
Section: Receptor Binding and Signallingmentioning
confidence: 99%
“…31 Recently, it was shown that sauvagine, a nonselective CRFR agonist, completely inhibited muscle atrophy in casted CRF1R knockout mice. 17 However, the same treatment with noncasted mice had no significant effect on muscle mass. 17 Amino acids were substituted in sauvagine and were tested in vivo in wildtype, CRF1R knockout, and CRF2R knockout mice, in both control and casted conditions.…”
mentioning
confidence: 96%
“…17 However, the same treatment with noncasted mice had no significant effect on muscle mass. 17 Amino acids were substituted in sauvagine and were tested in vivo in wildtype, CRF1R knockout, and CRF2R knockout mice, in both control and casted conditions. 17 Several CRF2R-selective sauvagine analogs were found to be more effective and potent than sauvagine in preventing atrophy due to casting.…”
mentioning
confidence: 96%
See 2 more Smart Citations